Analysis of the social and economic impacts of the Nusa Penida Festival on the local community - Pitanatri, Isvari Ayu; Wijana, Putu Ade; Mirayani, Ni Kadek Sri (Privietlab, 2025)
This study aims to analyze the social and economic impact of the Nusa Penida Festival on local communities in Nusa Penida, Bali. This annual festival showcases the cultural, artistic, and marine tourism of Nusa Penida, as well as the promotional media of the destinations and community empowerment. This study used a qualitative descriptive method and a case study approach. Data were collected through a literature review by examining various relevant secondary sources, such as scientific articles, government reports, and media publications. The results of the study showed that the Nusa Penida Festival has a positive contribution to local communities. From a socio-cultural perspective, this festival strengthens community identity and pride, encourages social participation, and increases awareness of the importance of cultural preservation. From an economic perspective, this festival encourages micro, small, and medium enterprise (MSMEs) activities, creates job opportunities, and increases local economic turnover. However, challenges such as decreased visitors, overtourism potential, and environmental pressure must be a concern in future management. Therefore, the Nusa Penida Festival must be directed toward the principle of sustainable tourism that emphasizes collaboration between government, community, and industrial actors so that the benefits can be distributed evenly and sustainably.